A serial mediation model of financial knowledge on the intention to invest: The central role of risk perception and attitude - Thien, Sang Lim; Rasid Mail; Mohd Rahimie Abd Karim; Zatul Karamah Ahmad Baharul Ulum; Junainah Jaidi; Raman Noordin (Elsevier, 2018)
Addressing the complexity of financial decision-making process, this study assessed the effects of financial knowledge towards the financial behavioural intention to invest with both risk perception and attitude, in serial, as mediators among young Malaysians. This study operationalized financial knowledge as actual financial knowledge (objective knowledge) and self-rated financial knowledge (subjective knowledge). Using purposive sampling strategy, this study sampled 492 respondents who were of below the prime-savings years for the questionnaire survey. The resultant outcomes of this study revealed significant mediating effects of risk perception and attitude in the sequential positive relationship between financial knowledge and financial behavioural intention to invest. Apart from the significance of financial knowledge in the financial decision-making process, this study also unravelled the complexity of the relationship of knowledge and behaviour with the combination of risk perception and attitude.